NextGen seasonal forecast system - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The NextGen system developed by ACToday is now operational in Guatemala and Colombia as a result of inter-institutional collaboration between ACToday, CIAT/CCAFS, and national partners.